Pengaruh Likuiditas Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Pertambangan Tahun 2019-2021 - arifudin, aldisa (Universitas Musamus,Merauke,Papua, 2023)
This research aims to determine the effect of liquidity and profitability on stock returns in mining companies in 2019-2021. The research approach used is quantitative research. The population used was 66 companies with samples taken using purposive sampling techniques. The data used in this research is secondary data involving 20 companies with 3 years of observation, so a sample of 60 data was obtained. The analytical tool used in this research is the SPSS version 26 program. The results of this research show that the liquidity variable measured using the Current ratio (CR) has no effect and is not significant on stock returns. Where the research results are tcount < ttable (-1.125 < 1.676), with a significance value > 0.05 (0.267 > 0.05). The profitability variable measured using return on assets (ROA) has a significant effect on stock returns. Where the research results show the value of tcount > ttable (2.269 > 1.676), with a significance value < 0.05 (0.028 < 0.05. The liquidity and profitability variables have an influence and are significant on stock returns. Where the research results show that fcount > ftable (3.256 > 3.20) with a value <0.05 (0.048 <0.05).Liquidity, Profitability, Current Ratio, Return On Assets, Stock Returns